Developing a Bilingual Guidebook for Istana Gebang Blitar - Ainun Chumairoh; Nur Safitri, Isnaini; Suyono, Achmad (Jurnal Pendidikan Bahasa, 2024)
Istana Gebang is a historical house that was once occupied by the family of the first president of the Republic of Indonesia, Bung Karno. Based on the survey, it is known that Istana Gebang does not provide a guidebook and some visitors have complained about the lack of information. Therefore, this research aims to develop a bilingual guidebook for Istana Gebang Blitar. This research is Design and Development Research which used the ADDIE development model. The research data collections methods are observation, interviews, and survey. The final result is the “Bilingual Guidebook of Istana Gebang Blitar” that consists of a cover, visitor regulations, table of contents, history of Istana Gebang, history of Bung Karno, descriptions of each collection, and contact information accompanied by images. The Bilingual Guidebook of Istana Gebang Blitar has been successfully developed. The researcher suggests that this bilingual guidebook be used as effectively as possible.